Solar Thermal System Evaluation in China - Xinyu Zhang; Wei Xu; Tao He; Shijun You; Yan Gao; Min Wang; Bojia Li (International Journal of Photoenergy)
More than 581 solar thermal systems (STSs), 98 counties, and 47 renewable application demonstration cites in China need to be inspected by the end of 2015. In this study, the baseline for performance and economic evaluation of STSs are presented based on the site test data and related references. An index used to evaluate STSs was selected, and methods to acquire the parameters used to calculate the related index were set. The requirements for sensors for testing were specified. The evaluation method was applied to three systems and the result shows that the evaluation method is suitable for the evaluation of STSs in China.